Philanthropic entities and religiosity on contemporary wandering comprehension - Do Nascimento, Eurípedes Costa [UNESP]; Justo, José Sterza [UNESP] (My University, 2014)
The wandering on the contemporary is a complex phenomenon in Brazilian culture in which the highway wanderers constitute one of its most radical examples by walking long-distances on foot and carrying on backs a sack with their belongings. Based on Foucault's studies about the pastoral power, this paper aimed to reveal the speeches and religious practices related to the wandering of Brazilian highway wanderers in housings maintained by two philanthropic entities in São Paulo State, Brazil, starting from managers' reports. Under point of religious view, the results indicated that wandering of highway wanderers is related to an unquestionable divine determination that related to the gospel preaching try to conform these individuals to the own life condition, beyond maintain them fixed in endless wandering on the Brazilian highways. Rethinking those philanthropic practices and charitable can favor the promotion of new knowledge in the daily of these attendance services to highway wanderers and the production of other senses for this subjectivation way of the present mobility conditions in the current world.
Entidades filantrópicas e religiosidade na compreensão da errância no contemporâneo
Keywords: Assistance; Institutional analysis; Religiosity